Developing an anti-crisis strategy to ensure the balanced potential of an enterprise - Lunkina, I. (Економічний вісник Донбасу, 2024)
The article considers the theoretical and methodological aspects of the formation of an anti-crisis strategy for ensuring the balanced potential of an enterprise, in particular the transport industry, in the context of economic transformation. The specifics of anti-crisis management, which are manifested in a comprehensive approach, orientation to the long-term perspective, flexibility and adaptability, as well as the maximum use of internal reserves and resources of the enterprise, are substantiated. The research of scientists who sought approaches to the formation of anti-crisis strategies and also made a significant contribution to the study of this issue is analyzed. A structural and logical scheme for the formation of an anti-crisis strategy is proposed, which consists of six main stages: determining the purpose of forming an anti-crisis strategy for enterprise management, assessing the influence of external factors on the formation of strategic goals, assessing the internal resilience of the enterprise to the crisis, analyzing the balance of the enterprise's potential, choosing strategic alternatives and implementing anti-crisis strategies for ensuring the balanced potential of the enterprise. Attention is paid to the development of a spatial model for choosing an anti-crisis strategy based on a three-dimensional matrix, which allows determining the position of the enterprise in the crisis space and choosing the optimal strategic alternatives. The main anti-crisis strategies are highlighted: activation and stabilization, concentration and differentiation, consolidation, modernization, restructuring and recovery strategy. The use of a three-dimensional matrix in the process of choosing an anti-crisis strategy allows the enterprise not only to avoid financial losses, but also creates the basis for long-term development and strengthening its positions in the market. The results of the study can be used to increase the resilience of enterprises to crisis, optimize the use of resources and ensure long-term development in conditions of market instability. У статті розглянуто теоретико-методичні аспекти формування антикризової стратегії забезпечення збалансованого потенціалу підприємства, зокрема транспортної галузі, в умовах трансформації економіки. Обґрунтовано специфіку антикризового управління, яка проявляється у комплексному підході, орієнтації на довгострокову перспективу, гнучкості та адаптивності, а також максимальному використанні внутрішніх резервів і ресурсів підприємства. Проаналізовано дослідження науковців, які шукали підходи до формування антикризових стратегій, а також внесли вагомий внесок у вивчення цього питання. Запропоновано структурно-логічну схему формування антикризової стратегії, яка складається з шести основних етапів: визначення мети формування антикризової стратегії управління підприємствам, оцінки впливу зовнішніх факторів на формування стратегічних цілей, оцінки внутрішньої стійкості підприємства до кризи, аналізу збалансованості потенціалу підприємства, вибору стратегічних альтернатив та реалізації антикризових стратегій забезпечення збалансованого потенціалу підприємства. Приділено увагу розробці просторової моделі вибору антикризової стратегії на основі тривимірної матриці, яка дозволяє визначити положення підприємства в кризовому просторі та обрати оптимальні стратегічні альтернативи. Виділено основні антикризові стратегії: активізація та стабілізація, концентрація та диференціація, консолідація, модернізація, реструктуризація та стратегія відновлення. Використання тривимірної матриці в процесі вибору антикризової стратегії дозволяє підприємству не лише уникнути фінансових втрат, а й створює основу для довгострокового розвитку та зміцнення позицій на ринку. Результати дослідження можуть бути використані для підвищення стійкості підприємств до кризових явищ, оптимізації використання ресурсів та забезпечення довгострокового розвитку в умовах нестабільності ринку.